Comparison of thoracic ultrasonography and thoracic radiography to detect active infectious bronchopneumonia in hospitalized dairy calves. (16th May 2021) - Berman, Julie; Masseau, Isabelle; Fecteau, Gilles; Buczinski, Sébastien; Francoz, David
Abstract: Background: The best test between thoracic ultrasonography (TUS) and thoracic radiography (TR) or the best combination of tests (series or parallel) to detect active infectious bronchopneumonia (BP) in hospitalized dairy calves remains unknown. Hypothesis/Objectives: To estimate performances of TUS and TR to detect active BP in hospitalized dairy calves and to determine the best strategy for using these tests based on a panel diagnosis method (PDM). Performances of TUS and TR were hypothesized to be equivalent. Animals: Fifty hospitalized dairy calves (≥7 days old; ≤100 kg; standing; pCO2  ≥ 53 mm Hg; any reason of presentation). Methods: Each calf prospectively and sequentially underwent physical examination, thoracic auscultation, blood analyses, and TUS and TR. Three blinded experts determined whether active BP was present/absent based on PDM. Krippendorff's alpha measured interexpert agreement. The sensitivities (Se) and specificities (Sp) of TUS and TR alone and in series or parallel were compared (McNemar's test; P  < .05). Results: Interexpert agreement was moderate at 0.58 (95%CI: 0.42; 0.73). The Se and Sp of TUS were 0.84 (95%CI: 0.60; 0.97) and 0.74 (95%CI: 0.57; 0.86), respectively. The Se and Sp of TR were 0.89 (95%CI: 0.67; 0.99) and 0.58 (95%CI: 0.39; 0.75), respectively. No significant difference was found in the Se and Sp of TUS and TR when analyzed alone, in series or in parallel. Conclusion: Thoracic ultrasonography or TR alone equally detected active BP in hospitalized dairy calves. Series or parallel analysis provided no additional benefit. Its ease of use and widespread accessibility support using TUS as a first‐line test to detect active BP in hospitalized dairy calves.